Abnormal Length and Position of the Sigmoid Colon and Its Clinical Significance - Nayak, SB; George, BM; Mishra, S (Kathmandu University Medical Journal, 2014)
Sigmoid colon is one of the most variable parts of the large intestine. Here we report a very rare type of variation of the sigmoid colon. This variation was observed during the routine dissections for undergraduate medical students at Melaka Manipal Medical College (Manipal Campus) India in September 2012. In the current case, the sigmoid colon was about 60cms long and made an inverted U shaped loop in front of the descending colon and the left kidney. It had a sigmoid mesocolon which covered the left kidney. The sigmoid colon had an ascending and a descending limb. This position of sigmoid colon and its mesocolon is dangerous as it can get twisted to form a volvulus. It also might cause confusions in radiologic and sigmoidoscopy techniques. DOI: http://dx.doi.org/10.3126/kumj.v10i4.11012 Kathmandu Univ Med J 2012;10(4):95-97